Residual Stress Measurement and the Slitting Method - Cheng, Weili; Finnie, Iain.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Residual Stress Measurement and the Slitting Method provides complete coverage of the slitting method with new results in analysis, computation and estimation. It discusses different roles of residual stresses from the fracture mechanics perspective. Covering both near-surface and through-thickness residual stress measurements, the book serves as a reference tool for graduate students, researchers and practicing engineers. The authors include discussions on the general expressions for residual stresses acting on the site of a slit, the analysis based on fracture mechanics solutions and finite element computations, the estimations using continuous and piecewise functions with and without least squares fit, examples of residual stress measurement and error analysis, the measurement of stress intensity factors, and many more timely topics. With more than 130 figures, Residual Stress Measurement and the Slitting Method provides detailed formulations and examples of compliance functions, weighted least squares fit and convergence test in stress estimation, and computer programs to facilitate the implementation of the slitting method. This book is an invaluable reference for professionals and researchers in the field.
to Residual Stresses -- Elements of Measurement Using the Slitting Method -- Compliance Functions for Near-Surface Measurement: The Body Force Approach -- Compliance Functions for Through-Thickness Measurement: The LEFM Approach -- Compliance Functions for Through-Thickness Measurement: The FEM Approach -- Estimation of Residual Stresses -- Measurement of Through-Thickness Residual Stress -- Measurement of Axisymmetric Residual Stresses -- Estimation Using Initial Strains -- Residual Stresses and Fracture Mechanics.
Keywords: Engineering; Continuum mechanics; Structural mechanics; Mechanical engineering; Engineering design; Machinery; Engineering; Structural Mechanics; Continuum Mechanics and Mechanics of Materials; Machinery and Machine Elements; Engineering Design; Mechanical Engineering; Electronic books